Utilization of Local Grass Cynodon dactylon for Football Field Rehabilitation and Minimizing the Incidence of Injuries - Rahayu, Rahayu; Mujiyo, Mujiyo; Herdiansyah, Ganjar; Herawati, Aktavia; Sutarno, Sutarno; Yang, Geun Mo; Hardian, Tiara; Istiqomah, Nanda Mei; Irmawati, Viviana; Romadhon, Muhammad Rizky; Hasanah, Khalyfah; Anggita, Akas (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2023)
The problems faced are uneven football field surface, uneven grass growth, many pebbles and boulders, stagnant and muddy during the rainy season and fractures in the soil during the dry season which make the field not of a good standard for use and have an impact on the incidence of injuries to field users. This study aims to improve the quality of grass for football field using quality local grass Cynodon dactylon in order to overcome the problem of bad fields and avoid field’s users injury. The method is through field rehabilitation technology by improving the surface design and soil media profile as well as the use of quality local grass. The rehabilitation technology includes improving the surface of the field to improve drainage by designing a “geger sapi” shape. The assessment of the rehabilitation results used a qualitative approach with a questionnaire survey to the local community of field users. The results of field grass rehabilitation make the quality of grass in the field after rehabilitation better growth by 45%, perception grass quality was very good by 43%, the surface of the field is flatter, no gravel and surface rocks are found so the flooded were not found by 83%. Field conditions with better grass quality also reduce the frequency of injuries incidents of player during competition about 61%. Hence, field grass rejuvenation benefits the environment and public health. This great benefit will increase the comfort and closeness between the local community.